Effects of Aging on Engineer's Satisfactions and Metal Health: Skill Obsolescence - Burke, Ronald J. (Academy of Management Journal, 1969)
Forty-three engineering managers completed a questionnaire dealing with sources of job and life strains, work satisfaction, and mental and physical well-being. The results showed that older engineers: (1) endorsed less positive or less favorable responses in general, and (2) were more likely to feel not fully qualified to handle their jobs.